The Potential of Sharia Pawnshops in Promoting Financing of Micro, Small and Medium Enterprises (Umkm) in South Sulawesi - Rahmah, Syahidah; Sigit, Muh. (Jurnal Ar-Ribh, 2024)
This study aims to find out how the potential of sharia pawnshops in encouraging the financing of Micro, Small and Medium Enterprises (MSMEs). The type of research used is a qualitative research method. The processed data is the result of interviews with sharia pawnshop employees in South Sulawesi. Data collection methods in this study are interviews, observation, Documentation Studies in which the authors go directly to see the conditions in the field. The results of this study indicate that the advantages of Islamic pawnshops in financing the MSME sector are: government owned, credit insurance, the process is easy, min -3 working days, guidance to customers but there are some things that need to be considered for MSME actors, namely they cannot take financing at sharia pawnshops when their business does not yet have a business license from the government and also there is no bookkeeping of the business being run so that the sharia pawnshop has difficulty in providing capital to MSMEs.